Synthesis of silver nanoparticles using marine macroalgae Padina sp. and its antibacterial activity towards pathogenic bacteria - Bhuyar, P.; Mohd Hasbi, Ab. Rahim; Sundararaju, Sathyavathi; Ramaraj, Rameshprabu; Maniam, Gaanty Pragas; Natanamurugaraj, Govindan (Elsevier, 2020)
Background: Marine algae used as a food source for ocean life and range in color from red to green to brown grow along rocky shorelines around the world. The synthesis of silver nanoparticles by marine alga Padina sp. and its characterization were fulfilled by using UV-visible spectrophotometer, Fourier transform infrared spectroscopy,scanning electron microscopy and field emission scanning electron microscopy, and energy-dispersive X-ray spectroscopy.